Female Bildungsroman In Contemporary Chinese Transnational Literature - Jiang, Ling (Pusat Pengajian Ilmu Kemanusiaan, 2019)
The recent decades witnessed the growing number of Chinese transnational novels (Ng & Holden, 2006), and some of them have achieved great success, especially those English novels written by overseas Chinese female writers and focusing on female bildungsroman. Yan Li and Xiaolu Guo are the most outstanding representatives. In this study, I explore the female bildungsroman in Chinese transnational literature in English written by overseas Chinese female writers. The two texts chosen for the study are A Concise Chinese-English Dictionary for Lovers (2008) by Chinese-British novelist Xiaolu Guo, and Daughters of the Red Land (1996) by Yan Li, a Chinese-Canadian writer. In my analysis, the development of the female protagonists in the two novels will be explored through the framework of transnational literature, which refers to the contemporary literature that has developed as a consequence of the transfer of information and ideas among different peoples, cultures and identities across a transnational field (Morgan, 2017).